PELATIHAN PENGENALAN KETERAMPILAN PRA MATEMATIKA YANG KREATIF DI TK ALQUR’AN TAQARRUB - Siti Fatimah Sihotang; Zuhri Zuhri; Tulus Rohana (LPPM Universitas Bina Bangsa, 2022)
Pre-mathematics is an important activity to train children to construct understanding with symbolic language called simple abstraction then teach children to understand the concept of numbers and number operations. One of the pre-mathematical activities or skills for early childhood is sorting and classifying (grouping activities). Sorting and grouping skills are very important because this activity can hone children's ability to observe similarities and differences. Unfortunately for the current condition of children, where the covid-19 pandemic is still ongoing which of course requires children to do a lot of activities at home, making early childhood children play less, especially understanding the importance of playing while learning. In fact, the introduction of playing and learning activities through pre-mathematical activities is very useful when children enter the elementary school (SD) level. Thus, seeing the importance of understanding pre-mathematical skills for teachers in Alqur'an Taqarrub Kindergarten to be taught to students, this service activity aims to provide information as well as improve pre-mathematical abilities and skills for teachers in Alqur'an Taqarrub Kindergarten. through pattern recognition, activity and classification of creative activities for early childhood, so that they can be directly applied and applied to students. The implementation method used is the Transfer of Knowledge with activity stages; 1) preparation; 2) Implementation; and (3) Evaluation. In general, PKM can run according to the schedule of activities and there is an increase in knowledge and skills about pre-mathematical skills, through creative activities. The teachers are also proven to have been able to understand various pre-mathematical skills and are able to make examples of creative and fun questions to teach students.